PENERAPAN DATA MINING DALAM MENGANALISA POLA KELAYAKAN SISWA UNTUK MASUK PADA KELAS UNGGULAN MENGGUNAKAN METODE KLASIFIKASI DENGAN ALGORITMA INTERACTIVE DICHTOMIZER TREE (ID3) PADA SMP NEGERI 1 GALANG - Yuda Perwira (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
The superior class at SMP N 1 Galang has been formed with an entrance examination conducted by SMP N 1 Galang to new students. Excellent classes that have been formed are still considered to be less effective because there are some students who do not have to be placed and there are students who do need to be placed in excellent classes. The design of the application to analyze the pattern of formation of superior classes that have been formed by the school can later analyze existing student data and create new patterns as a better reference later. The application of data mining using the Iterative Dichtomizer 3 (ID3) method in analyzing patterns in superior classes is expected to provide better results for schools in placing high achieving students in the superior classes later. This application will later provide new information in the form of patterns which can later be a proposal for the SMP N 1 Galang to analyze superior class data so that students who are placed in the class are indeed entitled to be placed in superior classes in the coming new school year.